2015
DOI: 10.1136/bjophthalmol-2015-307330
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and repeatability of foveal avascular zone measurements in healthy subjects by optical coherence tomography angiography

Abstract: FAZ area measurements by means of OCT-A showed excellent reproducibility and repeatability in healthy eyes. OCT-A is a non-invasive diagnostic method, and its reliability makes it an interesting potential diagnostic tool for disease detection and follow-up in retinal pathologies involving foveal microcirculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
116
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(129 citation statements)
references
References 21 publications
11
116
1
1
Order By: Relevance
“…Macular quantitative parameters vary across different instruments and techniques (i.e., manual versus automatic assessment); however, several studies demonstrated that they have a good inter-and intraoperator reliability in case of same machine, acquisition and postprocessing protocols. [7][8][9]11,12,23 Measurement at the superficial plexus is highly reliable, while manual demarcation at the deep plexus may be not easy due to less definite contours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macular quantitative parameters vary across different instruments and techniques (i.e., manual versus automatic assessment); however, several studies demonstrated that they have a good inter-and intraoperator reliability in case of same machine, acquisition and postprocessing protocols. [7][8][9]11,12,23 Measurement at the superficial plexus is highly reliable, while manual demarcation at the deep plexus may be not easy due to less definite contours.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that these parameters have high intraand interoperator reproducibility both in eyes with and without retinal diseases, for the same scan type and for the same machine. [7][8][9][10][11][12][13] In a study by Dong and coworkers, 14 a good agreement between 3 3 3-and 6 3 6-mm angiocubes was found for choriocapillary vessel density and for FAZ area at all retina vasculatures; conversely, reliability for retinal vessel density was weak. However, scan interchangeability has been only tested for small angiocubes and it remains uncertain for wider size scans (e.g., 12 3 12 mm).…”
mentioning
confidence: 99%
“…However, the mean age of the study population was 28.9 6 7.6 years, and there was no analysis of its variation in the different age groups. 35 In our Caucasian population, the superficial FAZ area was 0.28 6 0.10 for a mean age of 48.3 6 17.5 years. This small difference may be explained by our study population since we did not exclude patients with small or large FAZ areas (range, 0.086-0.554; Figs.…”
Section: Foveal Avascular Zonementioning
confidence: 99%
“…Evaluation of the reproducibility and repeatability of FAZ area measurements in young patients using OCT-A has been previously published. 35 Other studies concerned FAZ measurements in diabetic patients. 14,16,26,36 These studies have described the FAZ size and shape in healthy populations, but they used various imaging modalities and software, focused only on the FAZ at the level of the SCP, and did not distinguish between the different age groups.…”
Section: Foveal Avascular Zonementioning
confidence: 99%
“…Measurements of FAZ size (area and perimeter) using OCTA have been shown to be highly reproducible in patients with microcirculatory deficiency involving the macula, such as diabetic retinopathy, as well as in healthy individuals. 9,11 Using OCTA images of the superficial vascular network, our group has previously reported an enlarged FAZ area in the perifoveal region, which was spatially correlated with central visual field (CVF) loss in glaucoma patients. 12 Furthermore, our subsequent study demonstrated that the FAZ area and perimeter showed significant diagnostic value in discriminating glaucomatous eyes with CVF defects from normal eyes.…”
mentioning
confidence: 99%